Analysis of Precipitation Characteristics during 1957-2012 in the Semi-Arid Loess Plateau, China - Zhao, Weijun (PLoS One, 2015)
Precipitation is the only water supply and most important factor affecting vegetation growth on the slopes of semi-arid Loess Plateau of China. Based on precipitation data from 7 synoptic stations in the study area over the period 1957–2012, the trends of precipitation and standardized precipitation index (SPI) were analyzed by using linear regression, Mann−Kendall, and Spearman’s Rho tests at the 5% significance level. The results show that (1) the precipitation fluctuation of monthly precipitation was intense (coefficients of variation> 100%), and the drier years were recorded as 1965 and 1995 at all stations. (2) The significant change trend of different stations varied on different time scales: the Changwu station had a significant decreasing trend in April (−0.488 mm/year) and November (−0.249 mm/year), while Luochuan station was in April (−0.457 mm/year); Changwu station displayed a significant increasing trends in winter (0.220 mm/year) and a significant decreasing trends in spring (−0.770 mm/year). The significant decreasing trends in annual precipitation were detected at the Suide (−2.034 mm/year) and Yan’an (–2.129 mm/year) stations. (3) The SPI−12 series analysis suggests that the drought degree of Yulin and Changwu was the lowest and that of Hengshan was the highest among the 7 synoptic stations.